Diagnostic accuracy of pocket‐sized ultrasound for aspiration pneumonia in elderly patients without heart failure: A prospective observational study. Issue 12 (14th October 2021) - Yamanaka, Harumitsu; Maita, Hiroki; Kobayashi, Tadashi; Akimoto, Takashi; Osawa, Hiroshi; Kato, Hiroyuki
Abstract : Aim: To investigate the diagnostic accuracy of pocket‐sized ultrasound (PsUS) for aspiration pneumonia in elderly patients without heart failure. Methods: This prospective observational study included patients with aspiration pneumonia. PsUS was performed in six areas (bilateral chest, four dorsal areas) by an independent examiner, blinded to the computed tomography (CT) results as a reference standard. Patients with heart failure were excluded. Results: PsUS findings of 34 patients (median age, 87.5 years) and 204 areas were analyzed. Three or more B‐lines (comet tail artifacts) were strongly suggestive (positive likelihood ratio [LR+] 17.302) of consolidation on CT (CT‐consolidation, subpleural hypoechoic area with tissue‐like echostructure) or pleural change on CT. Consolidation on US (US‐consolidation) was suggestive of CT‐consolidation or pleural changes on CT (LR+ 6.453). Pleural effusion on US was strongly suggestive (LR+ 10.989) of CT‐consolidation or pleural change on CT. Absence of either three or more B‐lines, US‐consolidation, or US pleural effusion could not rule out CT‐consolidation or pleural change on CT (negative likelihood ratio [LR−] 0.482‐0.683). However, absence of all three findings could rule out abnormal CT findings (LR− 0.230). Chest radiograph findings proved difficult to confirm or exclude CT‐consolidation or pleural changes on CT (LR+ 1.584, LR− 0.489); when combined with PsUS findings, LR− improved to 0.124. Conclusions: Three or more B‐lines or US‐consolidation on PsUS in elderly patients with aspiration pneumonia without heart failure suggested CT‐consolidation or pleural changes on CT. When both PsUS and chest radiograph findings were negative, CT‐consolidation and pleural change could be excluded. Geriatr Gerontol Int 2021; 21: 1118–1124 .